2016
DOI: 10.1055/s-0036-1593772
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Outcomes following Total and Subtotal Tongue Reconstruction: A Systematic Review of the Contemporary Literature

Abstract: More than 45,000 Americans are diagnosed with oropharyngeal cancer annually and multimodal treatment often requires wide excision, lymphadenectomy, chemotherapy, and radiation. Total and subtotal lingual resection severely impairs speech, swallow, and quality of life (QoL). This study investigates functional outcomes and QoL following subtotal and total tongue resection with free tissue transfer reconstruction. A systematic review of the English language literature was performed using PubMed, Ovid, Embase, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
67
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(68 citation statements)
references
References 67 publications
0
67
0
1
Order By: Relevance
“…In general, patients with high motivation, good family support, and regular follow-up with both a physician and a speechlanguage pathologist develop better speech quality, swallowing ability, and overall quality-of-life after free-flap reconstruction of the tongue. 19,20 Speech and swallow therapy are also important in the preoperative setting. 20 In the search for the ideal reconstructive flap after glossectomy, multiple studies have evaluated speech, swallow, and quality-of-life outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In general, patients with high motivation, good family support, and regular follow-up with both a physician and a speechlanguage pathologist develop better speech quality, swallowing ability, and overall quality-of-life after free-flap reconstruction of the tongue. 19,20 Speech and swallow therapy are also important in the preoperative setting. 20 In the search for the ideal reconstructive flap after glossectomy, multiple studies have evaluated speech, swallow, and quality-of-life outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…18 Studies have demonstrated that, in large part, neotongues demonstrate no autologous motion but rather move based on movements of surrounding muscles of the pharynx. 19 Yoleri and Mavioğlu reported a case of tongue reconstruction using the gracilis muscle and obturator nerve, a flap often employed for facial reanimation. In their report, the neotongue regained some autologous movement; however, the patient unfortunately passed away before long-term evaluation could be completed.…”
Section: Reinnervationmentioning
confidence: 99%
See 3 more Smart Citations